Pemanfaatan Media Sempoa dalam Pembelajaran Matematika Bagi Guru SDN 01 Ulak Karang Selatan - Fazri Zuzano; Susi Herawati; Niniwati Niniwati; Syukmanetti Syukmanetti; Rita Desfitri; Khairudin Khairudin; Puspa Amelia; Yusri Wahyuni; Listy Vermana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
One effort to improve elementary school students' arithmetic (numeracy) skills is to use learning media in the form of an abacus. The abacus, also known as mental arithmetic, is a medium for developing thinking and calculating abilities in mathematics and is able to balance the abilities of the right and left brain. Therefore, SD 01 Ulak Karang teachers need to improve their skills in using the abacus, so that these skills can be mastered and provided to students well. The method of this activity includes basic level abacus training, namely (1) introducing body posture when using an abacus, (2) introducing the rules and how to operate/move the abacus beads, (3) introducing number notations represented by one or a group of abacus beads. (4) introduce the technique of calculating addition and subtraction using an abacus and practice questions. Based on the results of this activity, the teachers at SDN 01 Ulak Karang Selatan are familiar with the technique of calculating with an abacus and can use the abacus to carry out addition and subtraction operations correctly and quickly. The teachers were very enthusiastic about being able to master all the techniques and calculation operations with the abacus.